PENERAPAN MOTIF BATIK BERPOLA KOMBINASI BATIK TULIS REMEKAN PADA JAKET BOMBER DENGAN SUMBER IDE IKAN KOI - Tri Hariyanti; Urip Wahyuningsih (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
The research aims to develop patterned batik motifs through a combination of batik tulis and remekan techniques on bomber jacket clothing. The main idea comes from koi fish as a symbol of wealth and strength and a typical icon of Blitar City. The design process uses a three-stage creation method according to Gustami SP, namely exploration, design, and embodiment. Exploration is carried out through visual studies of koi fish, lotus flowers, and other supporting elements which are then developed into batik motifs. The design stage produces 6 motif designs on jackets, and patterned motifs on 250 x 115 cm fabric. The selected designs are realized through batik tulis and remekan techniques. The production process includes coloring, rolling, cutting materials, and sewing to become complete clothing. The results of the work show a combination of traditional artistic values ​​and contemporary design. Data collection was carried out through a questionnaire to 50 respondents to assess the selection of motifs and the assessment of the results of the design analysis aspects, motifs, colors, and final results. The majority of respondents stated that the work has high visual appeal. This work is an innovation in modern batik and encourages the interest of the younger generation in local culture.